INNOVATIVE TECHNOLOGIES IN EDUCATION: INTEGRATING VR AND AR INTO MODERN PEDAGOGY (Web of Teachers: Inderscience Research, 2026)
The modern educational paradigm increasingly competes with the immersive entertainment sector, necessitating novel pedagogical frameworks to sustain student engagement. Driven by rapid advancements in Virtual Reality (VR) and Augmented Reality (AR), this paper examines the integration of immersive technologies into school and university curricula. We propose a systematic framework that merges gamification with academic instruction to optimize cognitive retention. This study classifies VR/AR applications based on four distinct pedagogical scenarios—Linear, Interconnected, Creative Generation, and Collaborative Consolidation—and analyzes four primary implementation formats: in-person, distance, hybrid, and self-education. Special emphasis is placed on applying these technologies to foreign language acquisition and humanities. Finally, the paper discusses current technical and pedagogical challenges, offering strategic recommendations for future institutional adoption.